2009
DOI: 10.1037/a0014915
|View full text |Cite
|
Sign up to set email alerts
|

Attention problems, inhibitory control, and intelligence index overlapping genetic factors: A study in 9-, 12-, and 18-year-old twins.

Abstract: It is assumed that attention problems (AP) are related to impaired executive functioning. We investigated the association between AP and inhibitory control and tested to what extent the association was due to genetic factors shared with IQ. Data were available from 3 independent samples of 9-, 12-, and 18-year-old twins and their siblings (1,209 participants). AP were assessed with checklists completed by multiple informants. Inhibitory control was measured with the Stroop Color Word Task (Stroop, 1935), and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 93 publications
2
64
0
1
Order By: Relevance
“…Mean scores for groups of research patients with KS lie below normative averages on tests of general intelligence (Fales et al., 2003; van Rijn, Swaab, Aleman, & Kahn, 2008), and lower intelligence has been associated with poorer working memory and executive function in many studies in the general population (Ackerman, Beier, & Boyle, 2005; Ardila, Pineda, & Rosselli, 2000; Fales et al., 2003; Polderman et al., 2009; Salthouse & Pink, 2008), although these findings are not universal (Friedman et al., 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Mean scores for groups of research patients with KS lie below normative averages on tests of general intelligence (Fales et al., 2003; van Rijn, Swaab, Aleman, & Kahn, 2008), and lower intelligence has been associated with poorer working memory and executive function in many studies in the general population (Ackerman, Beier, & Boyle, 2005; Ardila, Pineda, & Rosselli, 2000; Fales et al., 2003; Polderman et al., 2009; Salthouse & Pink, 2008), although these findings are not universal (Friedman et al., 2006). …”
Section: Introductionmentioning
confidence: 99%
“…32 The results of one study showed an improvement in the ability to inhibit responses between the ages of 5 and 10 years. 27 This improvement remained significant after controlling for the influence of working memory and processing speed.…”
mentioning
confidence: 90%
“…[35][36][37][38] One of the studies 27 that assessed intelligence and inhibitory control (and the only study of this kind, using twins) enriches the field, since it showed that IQ is also shared with genetic factors. Also unique among the studies selected for this systematic review was a study…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies mentioned that the capacity of inhibition has a strong correlation with the fluid intelligence in adults (Polderman et al, 2009). Salthouse, Atkinson, and Berish (2003) found that the correlation between intelligence and inhibition occurs only at the age of 9, 12, and 18 years old.…”
Section: International Journal Of Research Studies In Psychology 79mentioning
confidence: 99%